Cover Picture: Uranium from German Nuclear Power Projects of the 1940s— A Nuclear Forensic Investigation (Angew. Chem. Int. Ed. 45/2015). Issue 45 (22nd September 2015) - Mayer, Klaus; Wallenius, Maria; Lützenkirchen, Klaus; Horta, Joan; Nicholl, Adrian; Rasmussen, Gert; van Belle, Pieter; Varga, Zsolt; Buda, Razvan; Erdmann, Nicole; Kratz, Jens‐Volker; Trautmann, Norbert; et al.
Abstract : Nuclear forensics was used to trace the history of two pieces of uranium metal, which are purported to originate from the first German nuclear reaction experiments in the 1940s. In their Communication onpage 13452 ff., M. Wallenius et al. compared the macroscopic sample properties with literature information and determined the production date and source of the uranium samples.